2003
DOI: 10.1161/01.cir.0000047274.66749.fe
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serum Soluble ST2 Receptor as a Novel Heart Failure Biomarker

Abstract: Background-Using genomic technology, we previously identified an interleukin-1 receptor family member, ST2, as a gene markedly induced by mechanical strain in cardiac myocytes. The soluble receptor form of ST2 is secreted and detectable in human serum. This study tested the hypothesis that soluble ST2 levels in the serum of patients with severe chronic heart failure are increased in patients with neurohormonal activation. Methods and Results-Serum samples, clinical variables, and neurohormone levels from the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
346
4
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 464 publications
(372 citation statements)
references
References 30 publications
11
346
4
11
Order By: Relevance
“…Increased serum levels of sST2 have been detected in a number of human diseases, including asthma and allergic airway inflammation, acute myocardial infarctions, and sepsis [10][11][12][13][14]. Although the biological significance for the increase in sST2 is not understood, several studies have demonstrated beneficial effects of sST2 treatment in animal models of diseases [2,4,6,15], suggesting that it may reduce inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum levels of sST2 have been detected in a number of human diseases, including asthma and allergic airway inflammation, acute myocardial infarctions, and sepsis [10][11][12][13][14]. Although the biological significance for the increase in sST2 is not understood, several studies have demonstrated beneficial effects of sST2 treatment in animal models of diseases [2,4,6,15], suggesting that it may reduce inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The secreted ST2 can be detected in serum from both mice and humans with mechanically overloaded hearts. Clinical and laboratory studies have confirmed that the soluble receptor is increased in the blood of patients with heart failure, and an increase in blood level over time reflects a worsening patient prognosis (91). The pathophysiology of ST2 in heart failure is undefined in part because the ligand for the receptor remains unidentified, but this genomic discovery approach shows how mechanically overloaded cultured cells can identify a new pathway and biomarker relevant to mechanically overloaded myocardium.…”
Section: Molecular Responses Of Cells and Tissues To Mechanical Stimulimentioning
confidence: 97%
“…Elevated levels of sST2 have been found in patients with inflammatory disorders associated with abnormal Th2 mediated responses, including autoimmune diseases [31], asthma [32,33], idiopathic pulmonary fibrosis [29], and sepsis [34]; sST2 levels are also found elevated in patients with other inflammatory conditions, like LPS induced inflammation [35] and myocardial infarction [36]. Additionally, sST2 has been proposed as a biomarker for heart failure [37].…”
Section: Introductionmentioning
confidence: 99%